A zero-net-mass-flux actuator for unmanned underwater vehicles. (15th July 2018) - Ayers, Bradley; Johari, Hamid
Abstract: A set of water tunnel experiments were conducted to establish the viability of a zero-net-mass-flux actuator as a maneuvering mechanism for unmanned underwater vehicles. The actuator, which consisted of a solenoid driving a piston in a cylindrical cavity, was enclosed in a streamlined model vehicle. The forces and moments on the model vehicle were measured by a six-axis load cell connected to the model through a sting. The actuator whose orifice axis was oriented perpendicular to the freestream was located near the aft end of the model. The time averaged thrust was measured for actuator frequencies up to 24 Hz and freestream velocities up to 8 m/s. In absence of freestream flow, scaling arguments indicate that the average thrust increases linearly with the actuator frequency, expelled mass and a characteristic expulsion velocity. The linear frequency dependence was verified experimentally up to a limit imposed by the solenoid response time. Thrust decreased linearly with increasing freestream velocity for values up to the characteristic velocity of actuator. An expression was developed for the time averaged thrust as a function of the actuator design, operating parameters, and freestream velocity. Highlights: A zero-net-mass-flux actuator is proposed for unmanned underwater vehicles. A model vehicle was tested in a water tunnel at velocities up to 8 m/s. Scaling arguments show that the actuator thrust increases linearly with frequency. Measurements revealed that thrust decreased with increasing freestream velocity. A correlation relates the actuator thrust with the design and operating parameters.